The peasants of Ottobeuren, 1487-1726 : a rural society in early modern Europe - Sreenivasan, Govind P. (Past and present publications., 2004)
The most detailed reconstruction to date of peasant society in early modern Germany, focusing on the lands of the Benedictine monastery of Ottobeuren. Based on a mass of archival data, the book argues that the German rural economy performed much better than has previously been believed.